Challenges to the implementation of business process re-engineering of the recruitment process in the Ministry of Fisheries and Marine Resources, Namibia - Swartz, Elizabeth Maraizia Joan (Stellenbosch : Stellenbosch University, 2018)
Thesis (MPA)--Stellenbosch University, 2018.